Whole genome sequencing reveals possible host species adaptation of Streptococcus dysgalactiae - Davide Porcellato (Nature Portfolio, 2021)
Abstract Streptococcus dysgalactiae (SD) is an emerging pathogen in human and veterinary medicine, and is associated with several host species, disease phenotypes and virulence mechanisms. SD has traditionally been divided into the subspecies dysgalactiae (SDSD) and subsp. equisimilis (SDSE), but recent molecular studies have indicated that the phylogenetic relationships are more complex. Moreover, the genetic basis for the niche versatility of SD has not been extensively investigated. To expand the knowledge about virulence factors, phylogenetic relationships and host-adaptation strategies of SD, we analyzed 78 SDSD genomes from cows and sheep, and 78 SDSE genomes from other host species. Sixty SDSD and 40 SDSE genomes were newly sequenced in this study. Phylogenetic analysis supported SDSD as a distinct taxonomic entity, presenting a mean value of the average nucleotide identity of 99%. Bovine and ovine associated SDSD isolates clustered separately on pangenome analysis, but no single gene or genetic region was uniquely associated with host species. In contrast, SDSE isolates were more heterogenous and could be delineated in accordance with host. Although phylogenetic clustering suggestive of cross species transmission was observed, we predominantly detected a host restricted distribution of the SD-lineages. Furthermore, lineage specific virulence factors were detected, several of them located in proximity to hotspots for integration of mobile genetic elements. Our study indicates that SD has evolved to adapt to several different host species and infers a potential role of horizontal genetic transfer in niche specialization.